In-vitro immunomodulatory activity of dragon fruit extract (Funded Work) - HARITHPRIYA.K,; JEYACHANDRAN.R, (International Journal of Pharma and Bio Sciences, 2019)
Dragon fruit (Hylocereus undatus (Haworth) Britton & Rose) a tropical variety which natively belongs to the Cactaceae (climbing cacti) family, commonly known as Pitaya, is most widely cultivated in Vietnam and in Southeast Asia. Because of the importance of pitaya in Indian systems of medicine and lack of adequate knowledge on immunomodulatory activity in living organism, present study is essential for this herbal medicine and its exploitation of biological significance possessed both peel and fruit pulps are hypothesized, which can be widely used as one of the key element in the field of pharmaceuticals, Siddha and also in food industries. The aim of this study is to determine the In-vitro Immunomodulatory profile of an edible and non-edible portion of Dragon fruit. In the present investigation of total phenol content and immunomodulatory potential in dragon fruit extract the methanolic non-edible extract showed higher phenolic content than other edible and non-edible ethanolic extract. The in-vitro lymphocyte proliferation of extracts against PBMC of sheep blood showed that the extracts with the increase in concentration will, in turn, increase the proliferation rate. Among which a higher concentration range of 2000 µg/ml non-edible methanolic extracts showed higher proliferation rate of 251.16% than other edible and non-edible extracts. From the result, it showed that the non-edible portion of Dragon fruit showed significant proliferation of lymphocyte present in the blood than the edible portion of Dragon fruit and the total phenol content was found to be high in non-edible methanolic extract of 44.85 GAE/mg like whereas the total phenol content was 19.33 GAE/mg in edible methanolic extract, 26.9 GAE/mg in non-edible ethanolic extract and 33.4 GAE/mg in edible ethanolic extract when determined using Folin Ciocalteu method. Thus, this work appears to be the preliminary in proving that the dragon fruit has the ability to modulate the immune system. This study serves as the model evidence for pharmaceutical and biotechnological industries to develop an immunemodulatory agent.